ANALYTICAL INVESTIGATION OF SOME CONSTRUCTIVE PARAMETERS OF A HOLDING MACHINE WITH TWO WORKING CAPACITIES CONNECTED BETWEEN EACH OTHER - ZALYUBOVSKYI, MARK; PANASYUK, IGOR (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The disadvantages of using machine mechanisms in the kinematic circuits of which contain a passive connection are described. A three-dimensional statically defined mechanism of the “Turbula” type machine without the presence of a passive connection in its kinematic circuit is proposed. This design of the machine is realized due to the introduction into the kinematic circuit of an additional moving link - the second working capacity. Operation of this design of the car allows to increase productivity of processing of details considerably due to the fact that there is a possibility on one car to carry out two different technological operations at the same time or to process two parties of various details at the same time. The principle of operation of the mechanism and the machine is described. Analytical researches of the basic geometrical and constructive parameters of the galvanizing machine with two working capacities which, as a whole, provide its rational functioning are executed. The relationship between the geometric parameters of the moving parts of the machine and the change in the amplitude of their movements. In particular, mathematical dependences are obtained, which make it possible to calculate the amplitude of the angle change between the axes of two tanks, as well as the amplitude of the distance change between mutually perpendicular geometric axes of the forks to the working tanks. The operation of this machine design will significantly increase the productivity of machining parts due to the fact that it is possible to perform two different technological operations on one machine or simultaneously process two batches of different parts. The obtained results of analytical researches can be used in the corresponding design bureaus of the machine-building enterprises at a stage of designing of the galting equipment with difficult spatial movement of working capacities.
Keywords: passive connection; kinematic circuit; connecting rod; shunting; working capacity